Vpliv značilnosti aspiracijskih referentov na proces prisvajanja novosti - Gorjup, Lina (Akademija MM, 2023)
This paper focuses on studying various characteristics of aspirational reference groups, i.e., groups to which consumers want to belong, on the process of adopting a new product. Based on a literature review, this paper recognizes the following traits of aspirational referents as vital in the process of adopting a new product: the referent’s expertise, attractiveness, trustworthiness, and the consumer’s identification with the referent. The paper examines how these characteristics influence the formation of consumers’ positive attitudes towards innovation as well as their intention to adopt a new product. While previous papers focused mostly on studying the direct effects of referents’ traits on consumer behaviour, this paper draws on models of communication effects to recognize the complexity of relationships among them. The results of a quantitative study on 171 respondents show that referent’s likability and trustworthiness strongly influence consumer’s positive attitude towards innovation, while the influence of consumer’s identification with a referent on a positive attitude is lower. Achieving the consumer’s trust in a chosen referent is important since trustworthiness mediates the influence of the referents expertise on the formation of a positive attitude. Increasing consumers positive attitude towards innovation is crucial, as well as it strongly influences consumer’s intention to adopt it. Likewise, the consumer’s identification with the referent also affects their intention to adopt the new product.
Keywords: aspiracijske referenčne skupine; lastnosti referentov; novosti; prisvajanje; Vedenje potrošnikov